Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Ad

Hi there,

Save hours of searching online or wasting money on unnecessary repairs by talking to a 6YA Expert who can help you resolve this issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

Here's a link to this great service

Good luck!

Posted on Jan 02, 2017

Ad

Let's take 2x^2 - 10x +12 and divide it by x-2.

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

__2x_-_6____________

x-2 ) 2x^2 - 10x + 12

2x^2 - 4x

------------

- 6x + 12

- 6x + 12

------------

0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

Oct 03, 2014 | Office Equipment & Supplies

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

We can write this polynomial as:

You can see this polynomial in following picture:

Notice that it intersects x axis for x=-2, 1 and 3 (because these are roots of polynomial).

- (x-(-2))*(x-1)*(x-3)=
- (x+2)(x-1)(x-3)=
- (x+2)[x*(x-3)-1*(x-3)]=
- (x+2)*(x^2-3x-x+3)=
- (x+2)(x^2-4x+3)=
- x*(x^2-4x+3)+2*(x^2-4x+3)=
- x^3-4x^2+3x+2x^2-8x+6=
- x^3-2x^2-5x+6

You can see this polynomial in following picture:

Notice that it intersects x axis for x=-2, 1 and 3 (because these are roots of polynomial).

Oct 03, 2011 | Office Equipment & Supplies

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

=>2x+3=0 ; taken x as common and 4-2=2 i.e. x(4-2) = 2x

=>2x=-3 ; +3's moved on the right-hand side, so it becomes -3

=>x=-3/2 ; 2 has been moved to the right-hand side and divided with -3 i.e 1/2 multiplied by -3 = -3/2

Good luck.

Thanks for using

Aug 13, 2010 | SoftMath Algebrator - Algebra Homework...

Hii,you can use the following solution
x^3 - 4x^2-12x=0
x(x^2-4x-12)=0
replacing -4x from -6x+2x
x(x^2-6x+2x-12)=0

Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

May 05, 2010 | Vivendi Excel@ Mathematics Study Skills...

The LG G20 DVD Rewriter is an advanced external burner that supports 'editable' Rewritable DVD+RW disk.

As a generic comment, not all writable/rewritable media are made equal and problem with branded & unbranded disks are not uncommon, so stick to brands that work for you for your specific unit!

The following is the advertised support for your unit, hope it helps:

**Reading Rate**
**DVD-R/-RW/-ROM**
16x/13x/16x/16xSL/12xDL max.
**DVD-RAM**
2x, 3x-5x, 6x-12x
**DVD-Video (CSS)**
4,8x max. (Single/Dual Layer)
**DVD+R/+RW**
16x/13x max./ 12xDL max.
**CD-R/RW/ROM**
48x/40x/48x max.
**CD-DA (DAE)**
40x max.
**Burning Speed**
**DVD-R**
2x, 4x CLV, 8xZCLV, 16x PCAV, 20X CAV
**DVD-RW**
1x, 2x, 4x, 6x CLV
**DVD-RAM**
2x, 3x ZCLV, 3x - 5x PCAV, 12x PCAV
**DVD+R**
2.4x, 4x, 8x, 12x, 16x PCAV, 20X CAV
**DVD+R Double Layer**
2.4x, 4x, 10x, 12x ZCLV
**DVD-R Dual Layer**
2x, 4x, 6x CLV, 10x, 12x ZCLV
**DVD+RW**
2.4x, 4x, 6x, 8x ZCLV
**CD-R**
4x, 8x CLV, 16x, 24x, 32x, 40x, 48x ZCLV
**CD-RW**
4x, 8x, 10x CLV, 16x CLV, 24x, 32x ZCLV

As a generic comment, not all writable/rewritable media are made equal and problem with branded & unbranded disks are not uncommon, so stick to brands that work for you for your specific unit!

The following is the advertised support for your unit, hope it helps:

Dec 28, 2009 | Computers & Internet

Hi,

Let's say your 3 numbers are a, b and c. Because they are consecutive and odd, you can write them like this:

a = 2x-1, b = 2x+1, c = 2x+3

Now, your problem looks like this:

2(2x-1)(2x+1) = (2x+1)(2x+3) + 7

2(4x^2-1) = 4x^2+6x+2x+3 + 7

8x^2-2 = 4x^2+8x+10

4x^2-8x-12 = 0

4(x^2-2x-3) = 0

x^2-2x-3 = 0

The solutions for this quadratic equation ( see more about this kind of equations here: http://en.wikipedia.org/wiki/Quadratic_equation ) are x=3 or x=-1. So, you've got two sets of solutions:

[1] a = 5, b = 7, c = 9

[2] a = -3, b = -1, c = 1

Take care,

Alex

Let's say your 3 numbers are a, b and c. Because they are consecutive and odd, you can write them like this:

a = 2x-1, b = 2x+1, c = 2x+3

Now, your problem looks like this:

2(2x-1)(2x+1) = (2x+1)(2x+3) + 7

2(4x^2-1) = 4x^2+6x+2x+3 + 7

8x^2-2 = 4x^2+8x+10

4x^2-8x-12 = 0

4(x^2-2x-3) = 0

x^2-2x-3 = 0

The solutions for this quadratic equation ( see more about this kind of equations here: http://en.wikipedia.org/wiki/Quadratic_equation ) are x=3 or x=-1. So, you've got two sets of solutions:

[1] a = 5, b = 7, c = 9

[2] a = -3, b = -1, c = 1

Take care,

Alex

Oct 15, 2009 | Google Computers & Internet

Hello,

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

Oct 01, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

80 people viewed this question

Usually answered in minutes!

×